The impact of rebranding on brand image and purchase intention : the case of Discover Airlines - Schwarz, Carmen Eva (2024)
Rebranding occurs with the change of elements of an established brand, e.g., the logo, to develop a differentiated market positioning and increase competitiveness. It can impact brand equity and, more precisely, brand image, the perception of a brand as reflected by the brand associations held in a consumer’s memory. However, in existing academia, it has been studied that rebranding and logo redesign can negatively affect consumers’ perceived brand image. This dissertation investigates the current rebranding and logo redesign of the Lufthansa airline Discover Airlines and the impact on consumer’s purchase intention and brand image. The logo before and after the rebranding acted as the stimuli and independent variable, and purchase intention was the dependent variable mediated by the brand image. At the same time, the customer status (customer vs. noncustomer of Lufthansa or Discover Airlines) was the moderator in the research design. An online survey was conducted where the stimuli were randomly presented to 167 respondents. The findings suggest an insignificant relationship between the logo and purchase intention, while the brand image fully mediates the interaction. Moreover, the brand image significantly impacts the purchase intention, while the customer status does not moderate the interactions—the brand image before the rebranding was perceived as more positive. This thesis contributes to the limited existing literature about rebranding. It provides a contemporary, practical insight into its impact on brand image/equity and purchase intention with the real-life current case of Discover Airlines and managerial insights.